Optimization and parametric economic analysis for carbon fiber reinforced plastic composites with Taguchi-present worth method - Oluwo, Adeyinka; Ogunmola, Bayo Yemisi; Oke, Sunday Ayoola; Rajan, John; Jose, Swaminathan; Lathashankar, Boluvar; Bolaji Aderibigbe, Samuel; Oluwaseun Odudare, Samson (Science, Engineering and Health Studies, 2025)
Within the drilling community, an integrated method of the technical and economic parameters is needed to improve profit margins and for sustainable operations. In this article, a novel framework that establishes the economic dimension of the drilling operation for the carbon fiber-reinforced plastic (CFRP) composites is presented by fusing the Taguchi method with the present worth method. The present worth, level, interest rate and the value of the optimal parametric setting at the various levels are integrated. Then the optimal points for variables are identified based on derivatives with response tables developed from the orthogonal array and signal-to-noise ratios with parametric ranking. The optimal parametric setting obtained using the Taguchi method was SP3PA1FR3TF1/TF3, matched against the optimal result of PW(i)SP3PW(i)PA3PW(i)FR3PW(i)TF2 for the present worth derivative with respect to n. The Taguchi method yielded 3000 rpm (speed), 100° (point angle), 500 mm/min (feed rate) and 84.23 N (thrust force). However, the optimal results for the present worth derivative with respect to i were interpreted as 3000 rpm (speed), 135° (point angle), 500 mm/min (feed rate) and 197.35 N (thrust force). Moreover, the optimal results regarding the derivative of present worth with respect to n are 1000 rpm (speed), 135° (point angle), 100 mm/min (feed rate) and 197.35 N (thrust force). In addition, when Oke and Fagbolagun’s model was deployed, the positions of the parameters/response with respect to the T-PW method’s evaluation were the thrust force (1st, -40.0460), spindle speed (2nd, -51.0999), point angle (3rd, -50.1034) and feed rate (4th, -50.2274). Thus, the work provides help to process engineers to control their operators and for budget planning purposes.